Epoxy resin composition and application thereof in electrically induced degumming

By using an epoxy resin composition and applying a DC voltage, electrically induced degumming is achieved, solving the problem of substrate damage caused by traditional methods, and achieving a low damage and controllable degumming effect.

CN119614121APending Publication Date: 2025-03-14SHENZHEN NO 1 FINE CHEM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411879300.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When traditional mechanical or chemical methods are used to degummate, it is easy to damage the substrate and lead to irreversible damage.

Method used

An epoxy resin composition is employed, which comprises an epoxy resin, a curing agent, accelerator, an ionic liquid, a conductive additive and an emulsifier, and electrically induced degumming is achieved by applying a DC voltage.

Benefits of technology

This method can achieve controllable degumming without destroying the composite material body, and under suitable humidity conditions, the degumming speed is fast and the power consumption is low, and it is suitable for a variety of disassembly needs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an epoxy resin composition and application thereof in electrically induced degumming, and belongs to the technical field of adhesive desorption materials. Electrically-induced desorption of the adhesive can be realized under the impressed current. According to the composition, a reversible oxide layer is formed on an adhesive interface by utilizing a chemical reaction generated by current induction, so that interface failure is caused, and degumming is realized. The method has the advantages that the controllability is high, controllable separation of a bonding body can be achieved under the low voltage, and the method is suitable for the surfaces of various base materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive desorption materials, in particular to an epoxy resin composition and application thereof in electrically induced debonding. Background Art

[0002] With the widespread application of lightweight composite materials, epoxy resin adhesives have been widely used in many industrial fields due to their excellent strength and durability. However, in some applications, such as aviation equipment, electronic packaging, 3C and automobile manufacturing, it is necessary to achieve controllable debonding of adhesives without damaging the substrate, while traditional mechanical or chemical methods are destructive and irreversible. Therefore, it is of great significance to provide a low-damage controllable debonding technology. Summary of the invention

[0003] The purpose of the present invention is to provide an epoxy resin composition and its application in electrically induced degumming, so as to solve the technical problem in the prior art that the substrate is destroyed and irreversible damage is formed due to degumming by mechanical or chemical methods.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides an epoxy resin composition, comprising the following components in parts by mass: 65-70 parts of epoxy resin, 3-6 parts of curing agent, 0.5-3 parts of accelerator, 15-20 parts of ionic liquid, 3-6 parts of conductive additive and 0.2-2 parts of emulsifier.

[0006] Furthermore, the epoxy resin includes one or more of bisphenol A epoxy resin, phenol novolac epoxy resin and solid o-cresol novolac epoxy resin.

[0007] Furthermore, the curing agent comprises dicyandiamide and / or diaminodiphenyl sulfone.

[0008] Furthermore, the accelerator includes organic urea and / or imidazole.

[0009] Further, the organic urea includes one or more of 3-phenyl-1,1-dimethyl urea, 1,3-diphenyl urea, 1,3-dimethyl urea, N-(3-chlorophenyl)-N',N'-dimethyl urea, DyhardUR 200, DyhardUR 300, Dyhard UR 500, Curithane 52, Curithane 75, Omicure U-24, Omicure U-410 and Omicure U-52M.

[0010] Further, the ionic liquid includes one or more of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium methanesulfonate, 1-ethyl-3-methylimidazolium ethanesulfonate, 1-ethyl-3-methylimidazolium difluorophosphate, 1-ethyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium formate.

[0011] Furthermore, the conductive additive includes one or more of polyethylene glycol, carbon nanotubes, graphene, carbon black, LiCl and NaCl.

[0012] Furthermore, the polyethylene glycol includes PEG400 and / or PEG600.

[0013] The present invention provides an application of an epoxy resin composition in electrically induced debonding, wherein a voltage is applied to the epoxy resin composition using a direct current power supply;

[0014] The voltage range is 2 to 10V.

[0015] Beneficial effects of the present invention:

[0016] The epoxy resin composition of the present invention can be used for disassembling packaging materials, electronic components, aviation structural parts and automotive composite material connection parts. By adjusting the voltage, current and humidity, the degumming rate can be controlled, which is suitable for various disassembly requirements. The electrically induced degumming process is concentrated at the interface and will not damage the composite material body. Under the condition of suitable humidity (40-60% RH), degumming is usually completed in a short time. In a high humidity environment, the composition shows a faster degumming rate and lower power consumption, which can achieve more efficient degumming applications. DETAILED DESCRIPTION

[0017] The present invention provides an epoxy resin composition, comprising the following components in parts by mass: 65-70 parts of epoxy resin, 3-6 parts of curing agent, 0.5-3 parts of accelerator, 15-20 parts of ionic liquid, 3-6 parts of conductive additive and 0.2-2 parts of emulsifier.

[0018] In the present invention, the added amount of the epoxy resin is preferably 68 parts by mass.

[0019] In the present invention, the amount of the curing agent added is preferably 4 to 5 parts by mass, and more preferably 4.5 parts by mass.

[0020] In the present invention, the amount of the accelerator added is preferably 1 to 2 parts by mass, and more preferably 1.5 parts by mass.

[0021] In the present invention, the amount of the ionic liquid added is preferably 16 to 19 parts by mass, and more preferably 18 parts by mass.

[0022] In the present invention, the amount of the conductive additive added is preferably 4 to 5 parts by mass, and more preferably 4.5 parts by mass.

[0023] In the present invention, the amount of the emulsifier added is preferably 0.5 to 1.5 parts by mass, more preferably 1 to 1.3 parts, and more preferably 1.2 parts.

[0024] In the present invention, the epoxy resin includes one or more of bisphenol A epoxy resin, phenol novolac epoxy resin and solid o-cresol novolac epoxy resin, preferably bisphenol A epoxy resin and / or phenol novolac epoxy resin, and more preferably bisphenol A epoxy resin and phenol novolac epoxy resin.

[0025] In the present invention, a liquid epoxy resin and a solid epoxy resin are preferably combined to improve toughness and combined density.

[0026] In the present invention, the curing agent comprises dicyandiamide and / or diaminodiphenyl sulfone, preferably dicyandiamide or diaminodiphenyl sulfone, and more preferably dicyandiamide.

[0027] In the present invention, the dicyandiamide can allow the curing process to proceed under mild conditions.

[0028] In the present invention, the diaminodiphenyl sulfone can improve the high temperature resistance of the composition.

[0029] In the present invention, the accelerator comprises organic urea and / or imidazole, preferably organic urea or imidazole, and more preferably organic urea.

[0030] In the present invention, the organic urea includes one or more of 3-phenyl-1,1-dimethyl urea, 1,3-diphenyl urea, 1,3-dimethyl urea, N-(3-chlorophenyl)-N',N'-dimethyl urea, DyhardUR 200, DyhardUR 300, Dyhard UR 500, Curithane 52, Curithane 75, Omicure U-24, Omicure U-410 and Omicure U-52M, preferably one or more of 3-phenyl-1,1-dimethyl urea, 1,3-diphenyl urea, Dyhard UR 200, Dyhard UR 300, Dyhard UR 500, Curithane 52 and Curithane 75, and more preferably Dyhard UR200, Dyhard UR 300, Dyhard UR 500, Curithane 52 and Curithane One or more of 75.

[0031] In the present invention, the Dyhard UR 200 contains 1,3-dimethylurea, which is suitable for medium temperature curing and good storage stability; Dyhard UR 300 contains 3-phenyl-1,1-dimethylurea, which is suitable for medium temperature curing, halogen-free, and high reactivity; Dyhard UR 500 contains 1,3-diphenylurea, which is suitable for high temperature curing and has the characteristics of halogen-free and fast curing. (2) Curithane series (Huntsman Company): Curithane 52, which contains a variety of phenyl and methyl substituted organic ureas, is widely used in medium and high temperature curing of epoxy resins; Curithane 75, which is mainly aimed at fast curing requirements and is suitable for electronic packaging materials. (3) Omicure series (CVC Thermoset Specialties): Omicure U-24, containing phenylurea accelerator, can significantly reduce the curing temperature of dicyandiamide and is suitable for low to medium temperature curing; Omicure U-410, containing 1,3-diphenylurea, is suitable for high temperature curing and improves heat resistance; Omicure U-52M, containing a variety of substituted ureas, is suitable for fast curing applications.

[0032] In the present invention, the organic urea is purchased from Alzchem of Germany.

[0033] In the present invention, the ionic liquid includes one or more of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium methanesulfonate, 1-ethyl-3-methylimidazolium ethanesulfonate, 1-ethyl-3-methylimidazolium difluorophosphate, 1-ethyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium formate, preferably 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium ethanesulfonate, 1-ethyl-3-methylimidazolium difluorophosphate, 1-ethyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium formate. One of ethyl-3-methylimidazolium methanesulfonate, 1-ethyl-3-methylimidazolium ethanesulfonate, 1-ethyl-3-methylimidazolium difluorophosphate, 1-ethyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium formate, further preferably 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium methanesulfonate or 1-ethyl-3-methylimidazolium ethanesulfonate, more preferably 1-butyl-3-methylimidazolium tetrafluoroborate.

[0034] In the present invention, the 1-butyl-3-methylimidazolium tetrafluoroborate has high conductivity efficiency and strong hygroscopicity. It is a high-conductivity ionic liquid with good ion migration ability under an electric field. The conductivity of its tetrafluoroborate anion is significantly improved in the presence of water, so relatively high humidity conditions can further increase its conductivity efficiency.

[0035] In the present invention, the 1-butyl-3-methylimidazolium hexafluorophosphate has high conductivity and strong hygroscopicity. Similar to 1-butyl-3-methylimidazolium tetrafluoroborate, it also has high ionic conductivity. Although its hygroscopicity is high, its water absorption capacity is slightly lower than that of BF4. - Anionic, and therefore more stable at relatively high humidity.

[0036] In the present invention, the 1-ethyl-3-methylimidazolium methanesulfonate has high conductivity and moderate hygroscopicity. Due to the presence of methanesulfonate, it can maintain high conductivity even under low humidity conditions. Compared with other types, it has lower hygroscopicity and is therefore more suitable for use in an environment with unstable humidity.

[0037] In the present invention, 1-ethyl-3-methylimidazolium ethanesulfonate has medium conductivity efficiency, medium hygroscopicity, good conductivity, and significantly improved conductivity under medium or high relative humidity conditions, and is suitable for applications that require stable operation under different humidity conditions.

[0038] In the present invention, the 1-ethyl-3-methylimidazolium difluorophosphate has medium conductivity efficiency and low hygroscopicity. The difluorophosphate has good stability and does not absorb moisture significantly. It is suitable for electrically induced degumming in a low humidity environment, but the conductivity is not significantly improved under high humidity conditions.

[0039] In the present invention, the 1-ethyl-3-methylimidazolium chloride has low conductivity and high hygroscopicity. Characteristics: Due to the presence of chloride anions, its conductivity is improved under conditions of high humidity, but its ion mobility is poor, and it is suitable for applications that require a slower degumming rate.

[0040] In the present invention, the 1-butyl-3-methylimidazolium formate has low conductivity efficiency, low hygroscopicity, and low conductivity at low humidity, and is not suitable for use under dry conditions, but can maintain relatively stable conductivity under high humidity conditions.

[0041] In the present invention, the conductive additive includes one or more of polyethylene glycol, carbon nanotubes, graphene, carbon black, LiCl and NaCl, preferably one or more of polyethylene glycol, carbon nanotubes, graphene and carbon black, and more preferably polyethylene glycol.

[0042] In the present invention, the carbon nanotubes, graphene, and carbon black are carbon-based materials, which have high electronic conductivity. They extend the electronic conduction path to a larger area in the colloid by forming a conductive network. They have strong stability, can significantly improve the conductivity of the system, have little plasticizing effect on the resin composition, and help improve the mechanical properties of the resin composition. However, carbon materials usually only provide electronic conductivity and may be weak in ionic conductivity. For the electrically induced degumming process, a single carbon-based material has limited effect, so it is often used in combination with other conductive additives.

[0043] In the present invention, the LiCl and NaCl can significantly increase the ionic conductivity of the system. They are easy to dissociate and can improve the ion concentration and ion mobility of the system. They have low cost and can significantly improve ionic conductivity, and are suitable for use in low-cost and high-requirement systems. However, salts may dissolve or precipitate in an environment with large humidity fluctuations, resulting in unstable conductivity of the system and poor stability.

[0044] In the present invention, the polyethylene glycol (PEG) comprises a mixture of one or more polyethylene glycols (PEG) of different molecular weights. Polyethylene glycols (PEG) of different molecular weights can also be used as conductive additives, and changes in molecular weight will affect conductivity, solubility and plasticizing effect. PEGs of different molecular weights can change the conductivity and physical properties of the system, and the specific effects and mechanisms are analyzed as follows: low molecular weight PEG (such as PEG200), low molecular weight PEG has higher fluidity and permeability, and can quickly distribute and evenly conduct current in the adhesive. Advantages: The conductivity may be higher, which enhances the free migration of ions in the system and can accelerate electrochemical reactions; Disadvantages: Low molecular weight PEG has a weak plasticizing effect on the epoxy matrix, which can easily cause insufficient flexibility of the system, and may cause stress concentration in the adhesive layer and affect the degumming process. Medium molecular weight PEG (such as PEG400 to PEG600): Medium molecular weight PEG has achieved a good balance between conductivity and plasticization, and can effectively enhance conductivity while ensuring the flexibility of the system; Advantages: Good conductivity and plasticization effect, more suitable for use in systems with a balance between stress requirements and conductivity; Disadvantages: Performance may fluctuate greatly in environments with large humidity changes. High molecular weight PEG (such as PEG1000 and above): High molecular weight PEG diffuses slowly in colloids and is more suitable for systems that need to increase viscosity or bonding strength, but its gain on conductivity is small; Advantages: Provides a better plasticization effect in systems with high viscosity and rheology requirements; Disadvantages: Weak conductivity, because high molecular weight will hinder ion migration, resulting in a slower current conduction rate in the system.

[0045] In the present invention, the polyethylene glycol includes PEG400 and / or PEG600, preferably PEG400.

[0046] In the present invention, the emulsifier is preferably Gransurf77, which is a silicone emulsifier. Its surface active molecular structure plays a role in stable dispersion and interface wetting in the system. The main role of the emulsifier in the electrically induced degumming formula is to improve the compatibility between the ionic liquid and the epoxy resin matrix, promote the uniform distribution of the conductive additive in the system, and adjust the rheological properties of the resin composition. Improve the compatibility of ionic liquids and epoxy resins: Due to the different polarities and chemical properties of ionic liquids and epoxy resins, direct mixing may lead to poor compatibility, resulting in uneven distribution of ionic liquids in the epoxy matrix. Gransurf77, as an emulsifier, can reduce the stratification phenomenon caused by poor compatibility, allowing the ionic liquid to be more evenly dispersed in the epoxy resin matrix, thereby improving the conductivity and stability of the entire system. Promote the uniform distribution of conductive additives: Gransurf77 reduces the interfacial tension, making the conductive additives (such as ionic liquids, conductive nanoparticles, etc.) more evenly distributed in the epoxy matrix to avoid aggregation. This uniform distribution helps to form a stable conductive network under the action of the electric field and improve the current conduction efficiency during the degumming process. Regulate the rheological properties of the adhesive: The addition of Gransurf77 can adjust the viscosity and fluidity of the epoxy resin composition, so that the entire resin system exhibits more ideal flexibility and plasticity when the electric field is applied, thereby reducing the cracking problem caused by local stress concentration and improving the controllability and repeatability of degumming. In general, in the electrically induced degumming formula, the main role of Gransurf77 is to improve the compatibility of ionic liquids and epoxy resins, promote the uniform distribution of conductive additives, and adjust the rheology of the adhesive, making the electrically induced degumming process more efficient and controllable; its mechanism is based on the interfacial wetting effect of the emulsifier, which reduces the interfacial tension of different components, ensures the uniform distribution of the conductive components, forms a stable conductive channel, and achieves more ideal degumming performance when the electric field is applied.

[0047] The present invention provides an application of an epoxy resin composition in electrically induced debonding, wherein a voltage is applied to the epoxy resin composition using a direct current power supply;

[0048] The voltage range is 2-10V, preferably 3-7V, and more preferably 5V.

[0049] In the present invention, the application of the epoxy resin composition in electrically induced debonding includes the controllable bonding and disassembly of electronic components (such as mobile phone batteries), automobile parts and the like. The controllable debonding of the bonded parts is achieved by applying voltage, which is particularly suitable for occasions requiring high precision and controllable disassembly, such as replacement of mobile phone batteries. During the debonding process, the anode at the interface, the ionic liquid and the metal surface undergo an electrochemical reaction to generate oxides, and the oxides expand to induce stress, resulting in the controllable separation of the bonded parts.

[0050] In the present invention, the application of the epoxy resin composition in electrically induced debonding includes electrically induced debonding of epoxy resin glass fiber composite material plates, including controllably disassembled composite material structures, which are widely used in aerospace, automobile manufacturing and other fields.

[0051] In the present invention, the application of the epoxy resin composition in electrically induced debonding includes the controllable disassembly of carbon fiber composite materials, such as the disassembly of composite material structures in aviation and automobile manufacturing.

[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] 44 parts of liquid bisphenol A epoxy resin 128, 25 parts of phenol novolac epoxy resin 631, 6 parts of dicyandiamide and 0.5 parts of 2-methylimidazole were mixed uniformly at 60° C. in a double planetary mixer, and then 18.5 parts of 1-ethyl-3-methylimidazole ethanesulfonate, 5.5 parts of polyethylene glycol 400 and 0.5 parts of Gransurf77 were added, and the mixture was fully stirred until uniform. Then, a press was used to discharge and package the mixture to obtain an epoxy resin composition, which was stored at 0° C. for future use.

[0055] After the adhesive is thawed, apply it to the bonding surface of the mobile phone battery module and the mobile phone frame or mobile phone structural parts, butt the bonding surface, and apply 5N / cm 2 The bonding parts are placed in a constant temperature box and heated to 120°C for 2 hours to complete the curing.

[0056] Use 2V direct current to introduce current into the bonding interface and achieve debonding within 2 minutes.

[0057] Example 2

[0058] 30 parts of liquid bisphenol A epoxy resin 128, 20 parts of solid bisphenol A epoxy resin 901, 19.5 parts of solid o-cresol epoxy resin 704, 5 parts of dicyandiamide and 1 part of 1,3-diphenylurea are mixed evenly under a double planetary mixer, and then 18.5 parts of 1-ethyl-3-methylimidazol ethanesulfonate, 5.5 parts of polyethylene glycol 400 and 0.5 part of Gransurf77 are added, and the mixture is fully stirred until uniform. Then, a press is used to discharge and package the mixture to obtain an epoxy resin composition.

[0059] The prepared epoxy resin composition is subjected to a hot-melt two-step prepreg production line, and the resin film coated with epoxy resin is compounded with glass fiber woven cloth, so that the glass fiber is fully impregnated to form epoxy resin glass fiber prepreg with electrically induced degumming;

[0060] Two layers of epoxy resin glass fiber prepreg with electrically induced debonding were sandwiched between two layers of aluminum foil to ensure that the glass fiber prepreg was in full contact with the aluminum foil, and a hot press was used to apply a pressure of 0.5 MPa while heating to 120° C. for 2 hours to complete curing, thereby forming an epoxy resin glass fiber composite material sheet;

[0061] Take two epoxy resin glass fiber composite materials, apply the prepared epoxy resin composition adhesive film (same formula) to the surfaces to be bonded of the two plates, butt the two plates together and apply 5N / cm 2 The curing was completed by heating at 120°C for 2 hours.

[0062] A 5V DC voltage was applied between the bonded composite sheets at 0.5mA / cm 2 Under the condition of , the current is passed, and at the interface anode, the ionic liquid reacts electrochemically with the surface of the aluminum foil to generate aluminum oxide or aluminum hydroxide, which diffuses to the bonding interface. The expansion of the oxidation product generates interfacial stress, resulting in bonding failure and debonding between the plates. The entire debonding process is completed within 5 minutes, and there is no obvious damage to the surface of the aluminum foil and glass fiber.

[0063] Example 3

[0064] 30 parts of liquid bisphenol A epoxy resin 128, 20 parts of solid bisphenol A epoxy resin 901, 17.5 parts of solid o-cresol epoxy resin 704, 5 parts of dicyandiamide and 1 part of 3-phenyl-1,1-dimethylurea are mixed uniformly at 60° C. in a double planetary mixer, and then 20 parts of 1-butyl-3-methylimidazole hexafluorophosphate, 5 parts of carbon nanotubes and 0.5 parts of Gransurf77 are added, and the mixture is stirred thoroughly until uniform to obtain an epoxy resin composition.

[0065] The prepared epoxy resin composition is coated into an epoxy resin film by a hot melt method, and is laid on the surface of a carbon fiber prepreg made of a conventional epoxy resin matrix resin that does not have electrically induced debonding. Multiple layers of carbon fiber prepreg are stacked with the electrically induced debonding epoxy resin film of the present invention, and heated to 120° C. with a hot press at a pressure of 0.5 MPa for 2 hours to form a carbon fiber composite material plate.

[0066] The prepared electrically induced debonding epoxy resin film was laid between two carbon fiber composite plates. The plates were pressed together and 4N / cm 2 of pressure and heated at 120°C for 2 hours to complete the bonding.

[0067] A voltage of 10 V was applied between the two bonded carbon fiber composite sheets, and a DC current of 2 mA / cm was passed. 2At the anode at the interface, the electrochemical reaction generates oxides including titanium oxide and aluminum oxide, which diffuse into the bonding layer. The interfacial stress gradually accumulates, the bonding fails, and the debonding is completed within 7 minutes. After disassembly, there is no obvious damage on the surface of the plate.

[0068] Embodiments 4 to 6

[0069] Different from Example 1, in Examples 4 to 6, the humidity conditions of the storage environment of the epoxy resin composition were controlled to be 0% RH, 29% RH and 53% RH respectively to adjust the water content of the composition. In the degumming experiment, the sample was placed in a constant temperature and humidity chamber in advance, and the oxidation reaction of the anode interface and the adhesion failure were observed after the current was applied. The results showed that the degumming time of Examples 4 to 6 was 28 minutes, 10 minutes and 5 minutes respectively.

[0070] As can be seen from the above embodiments, the present invention provides an epoxy resin composition and its application in electrically induced debonding. Experiments show that the composition can achieve stable debonding within a voltage range of 2 to 10 V. The higher the humidity, the more obvious the electrochemical reaction, and the greater the adhesive interfacial stress caused by the current-induced anodic oxidation reaction, thereby achieving a fast and low-damage debonding effect, solving the technical problem of the substrate being destroyed and irreversible damage caused by mechanical or chemical debonding in the prior art.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An epoxy resin composition, characterized in that The invention comprises the following components in parts by weight: 65-70 parts of epoxy resin, 3-6 parts of curing agent, 0.5-3 parts of accelerator, 15-20 parts of ionic liquid, 3-6 parts of conductive additive and 0.2-2 parts of emulsifier.

2. An epoxy resin composition according to claim 1, characterized in that: The epoxy resin includes one or more of bisphenol A epoxy resin, phenol novolac epoxy resin and solid o-cresol novolac epoxy resin.

3. An epoxy resin composition according to claim 1, characterized in that: The curing agent comprises dicyandiamide and / or diaminodiphenyl sulfone.

4. An epoxy resin composition according to claim 1 or 2, characterized in that: The accelerator includes organic urea and / or imidazole.

5. An epoxy resin composition according to claim 3, characterized in that: The organic urea includes one or more of 3-phenyl-1,1-dimethyl urea, 1,3-diphenyl urea, 1,3-dimethyl urea, N-(3-chlorophenyl)-N',N'-dimethyl urea, Dyhard UR200, Dyhard UR 300, Dyhard UR 500, Curithane 52, Curithane 75, Omicure U-24, Omicure U-410 and Omicure U-52M.

6. An epoxy resin composition according to claim 1, characterized in that: The ionic liquid includes one or more of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium methanesulfonate, 1-ethyl-3-methylimidazolium ethanesulfonate, 1-ethyl-3-methylimidazolium difluorophosphate, 1-ethyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium formate.

7. An epoxy resin composition according to claim 1 or 6, characterized in that: The conductive additive includes one or more of polyethylene glycol, carbon nanotubes, graphene, carbon black, LiCl and NaCl.

8. An epoxy resin composition according to claim 7, characterized in that: The polyethylene glycol includes PEG400 and / or PEG600.

9. Use of an epoxy resin composition according to any one of claims 1 to 8 in electrically induced debonding, characterized in that: applying a voltage to the epoxy resin composition using a DC power supply; The voltage range is 2 to 10V.

Citation Information

Cited By

  • Repairable electrolytic adhesive heat-conducting structural adhesive as well as preparation method and application thereof

    CN120865823A